Cultural And Social Dynamics In Arabic Language Education: An Analysis In Urban And Rural Settings - Ahmadi, Ahmadi; Nashihin, Husna; Prahastiwi, Eka Danik; Alquriyah, Yusroh; Ead, Hamed A. (Ijaz Arabi Journal of Arabic Learning, 2025)
This study examines the cultural and social dynamics influencing Arabic language education in urban and rural settings. It investigates how environmental factors, cultural values, and social interactions shape language acquisition and teaching methodologies. The research employs a comparative qualitative approach, incorporating observations, interviews with educators and learners, and an analysis of educational practices in both contexts. Findings reveal significant differences between urban and rural settings: urban environments benefit from diverse populations, access to advanced technology, and collaborative learning opportunities, while rural areas face challenges such as limited resources but leverage strong community involvement and cultural continuity. The study concludes that contextually responsive strategies, culturally aligned curricula, teacher training programs, and integrating modern tools with traditional practices are essential for effective and sustainable Arabic language education. These results provide actionable insights for policymakers and educators aiming to enhance the accessibility and relevance of Arabic language programs across diverse learning environments.